Niger : Second Public Expenditure Management and Financial Accountability Review, Volume 2. Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
The second public expenditure management and financial accountability review (PEMFAR II) report provides analysis of the fiscal space outlook, a review of public expenditure management, including of the public investment management system, and assessments of the public financial management and public procurement systems. The review covers the period since the 2004 PEMFAR until 2009 and the detailed analysis of public expenditures focuses on three key sectors (education, health and rural development) which represented about 52 percent of the voted budget in 2007 and 2008 and are the pillars of Niger's second poverty reduction strategy paper (PRSP II). The PEMFAR II a comprehensive short and medium term (2010-2012) reform agenda which will assist the Government to prepare and adopt an action plan to improve the effectiveness of public resources management in Niger. This report constitutes the main report (volume one) of the PEMFAR II. Volume two of the PEMFAR II provides the detailed report of the evaluation of the public procurement system. The summary, after the above overview, reflects the underlying themes that emerge from the assessments of fiscal space outlook, public expenditures including public investment management, the public financial system, and the public procurement system. At the end, the summary a set of targeted priority actions aimed at improving the developmental impact of public expenditures.